Perbandingan Aktivitas Antibakteri 4-Metilpiperazin-N-Karbonil Ampisilin dengan Ampisilin Terhadap Micrococcus luteus dan Escherichia coli - Pudjianto, Andreyanus Eko; Ervina, Martha; Caroline, Catherine; Soekardjo, Bambang; Foe, Kuncoro (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2013)
Piperacillin has antimicrobial action but it is not absorbed from gastrointestinal tract Therefore, it needs structure modification to increase its absorption while keeping its antimicrobial action. The 4-methylpiperazin-N-carbonyl ampicillin was the product of reaction between ampicillin and 4-methylpiperazin-N-carbonyl chloride using Schotten Baumann method. The aim of this research was to compare the antibacterial activity between 4-methylpiperazin-N-carbonyl ampicillin and ampicillin. The comparison test of antibacterial activity was done with Kirby-Bauer disk diffusion susceptibility method on Mueller-Hinton agar which had been inoculated with Micrococcus luteus and Escherichia coli. Based on orientation studies, concentration of 4-methylpiperazin-N-carbonyl ampicillin and ampiCillin were 0.5 ppm against Micrococcus luteus and 500 ppm against Escherichia collin order to get visible zone of inhibition. The results showed that 4-methylpiperazin-Ncarbonyl ampicillin had lower antibacterial activity than ampicillin which was showed by its zone of inhibition which was lower compared to ampicillin in inoculated agar media of Micrococcus luteus and Escherichia coli.